KEANEKARAGAMAN JENIS MAKROZOOBENTOS DIMUARA SUNGAI NIPAH KECAMATAN PERBAUNGAN KABUPATEN SERDANG BEDAGAI SUMATERA UTARA - Siamtupang, Lestari Lidya Octaviani; Kardhinata, E. Harso; ZNA, Hanifah Mutia (Program Studi Biologi, Fakultas Biologi Universitas Medan Area, 2017)
This research was conducted to determine the species diversity of macrozoobenthos and determine the condition of physical and chemical factors in the waters of estuary river inÂ Nipah Village Perbaungan District Serdang Bedagai Sumatera Utara. The result of diversity of macrozoobenthos obtained 28 species with one phylum, 2 class, 7 orders, 18 families and 20 genera. Measurement of physical and chemical factors waters obtained an average pH 7 both ebb and tide conditions; in conditions of salinity waters receded an average of 0 and at high tide the average of 5; the ebb and tide conditions an average temperature of 27-30Â°C; Average current speed 10,5-19,1 cm/s; Brightness average water 14-16,3cm; and an average depth of 40,3-150cm. Values obtained by the abundance of species which are 3378-5322 ind/m2. Macrozoobenthos types that dominate the river mouth Nipah are gastropods. Values Diversity Index (H ) macrozoobenthos of 2.152 to 2.762 were classified into well water. Uniformity index (E) showed a value of 0.397 to 0.532 (deployment is not uniform or uneven). Value Dominance Index (C) showed a value of 0.074 to 0.170 (the dominance of low or no kind dominance). In general, relatively good water conditions and suitable for life macrozoobenthos.